Analisis Terapan Persetujuan Tindakan Medik Pada Pasien Anak dan Dewasa di RSU Cut Mutia - Khairunnisa, Cut; Fardian, Nur; Mauliza, Mauliza; Rizaldy, Muhammad Bayu (Universitas Pahlawan Tuanku Tambusai, 2024)
Medical approval is part of the therapeutic agreement that occurs between doctors and patients. Approval of medical procedures is carried out on high-risk medical procedures by doctors such as surgery and anesthesia. After both parties agree, the approval of medical action must be signed by both parties, both doctors and patients. This study aims to analyze the implementation of medical action approval carried out at RSU Cut Mutia, North Aceh Regency. This study involved 30 participants who conducted indept interviews, and the data was analyzed qualitatively. The results of the study found four themes in the application of medical action approval at RSU Cut Mutia, namely: The level of understanding and knowledge that is lacking on the part of patients and their families, the use of medical language or terms by doctors, the clarity of information provided by doctors, the absence of witnesses from the patient in signing medical action approvals.